Bioethical Aspects of Rehabilitation Clinical Practice: A Comparative Study between Opinions of Staff and Patients in Acute and Chronic Stage Departments. Issue 2 (2020) - Koleva, Ivet; Yoshinov, Borislav; Gerenova, Julieta; Dimitrov, Todor; Alexiev, Alexander; Yoshinov, Radoslav R.
No abstract available